Synthesis of Chlorophyll–Thiophene Conjugates through Friedel–Crafts Reaction - Kichishima, Saki; Nishikawa, Takeru; Tamiaki, Hitoshi (Synthesis, 2025)
Friedel–Crafts reactions of a chlorophyll-a derivative possessing a hydroxymethyl group at the 3-position with (benzo)thiophenes in the presence of p-toluenesulfonic acid gave 3-(benzo)thienylmethyl-chlorins regioselectively. The α-position of unsubstituted thiophene was more reactive toward the acid-assisted dehydration reaction than the β-position. Electron-donating substituents at the β-position in thiophene were acceptable for the production of the α-adducts, but electron-withdrawing substitution on the thiophene core proved ineffective. The electron-rich α,α′-dimethylthiophene could not be substituted at the β-position with the (chlorin-3-yl)methyl group. The reaction with benzothiophene exclusively afforded the β-substituted adduct. The reverse regioselectivity was consistent with the conventional electrophilic substitutions of (benzo)thiophenes. Under the aforementioned Friedel–Crafts reaction conditions, the α-methylation of benzothiophene led to the β-adduct as expected, whereas its β-methylation resulted in the successful preparation of the α-adduct. The fusion of a benzo moiety on thiophene largely affected the reactivity and regioselectivity toward the production of the chlorophyll–thiophene conjugates.
Keywords: chlorin π-system; dehydration adduct; electrophilic substitution; heteroaromatic; methyl pyropheophorbide-a; regioselectivity